314 Vimentin Stain: A Useful Stain or an Ancient Change. (11th January 2018) - Yang, Yu; DeYoung, Barry; Qasem, Shadi
Abstract: Objectives: Vimentin is an intermediate filament protein widely expressed in mesenchymal tumors as well as various types of nonmesenchymal tumors. It is also believed to be a marker for epithelial to mesenchymal transition. Historically, vimentin has often been used as a quality control for immunohistochemical stains (IHC); however, with improvement of IHC techniques, this is rarely needed nowadays. In this project, we attempted to review the use of vimentin in our institution and its utility in various diagnostic scenarios. Methods: We retrospectively reviewed the pathology archives in our institution for all specimens with vimentin stain between 2000 and 2016. The cases were classified into epithelial, hematolymphoid, melanocytic, mesenchymal, and unclassified groups, and the staining results were categorized as positive, negative, or unknown, based on the pathology report. Diagnostic comments were reviewed in order to make a judgement of whether vimentin was helpful or not for each individual case. Results: A total of 361 specimens with vimentin stains were retrieved. Vimentin was positive in 96% of mesenchymal, 71% of epithelial, 100% of hematolymphoid, 96% of melanocytic, and 91% of unclassified cases. Vimentin was found to be helpful in only 43% of the cases. Of the 136 helpful cases, the majority (85%) was epithelial. Helpful scenarios included the work-up for metastatic carcinomas, differentiating renal and gynecologic tumors, and tumors with divergent differentiation (eg, carcinosarcoma, sarcomatoid carcinoma). Conclusion: Vimentin is positive in a wide variety of tissue types and not specific for mesenchymal tumors. It is most helpful in differentiating certain types of carcinomas. Pathologists need to evaluate their use of ancillary techniques, especially in the era of value-based care.